Adsorption of rare gases on the C20 nanocage: a theoretical investigation. (7th March 2018) - Rahimi, Rezvan; Kamalinahad, Saeedeh; Solimannejad, Mohammad
Abstract: The adsorption of rare gases (Rg) on the external surface of pristine and Sc-doped C20 (ScC19 ) nanocage is investigated using density functional theory (DFT). Also, time-dependent density functional theory (TD-DFT) and natural bond orbital (NBO) calculations are performed at the CAM-B3LYP/6-31G (d) level. The NBO analyses indicate that the adsorption of Rg molecules with studied nanocage significantly alters its electronic nature. Theoretical results have shown that Rg is weakly adsorbed on the pristine C20, so this nanocage cannot be a proper sensor for detecting and sensing rare gases. In order to improve properties of the nanocage as a promising sensor, Sc-doping process was investigated. The more negative adsorption energies (Eads ) of Rg/ScC19 means that adsorption of Rg on the surface of ScC19 is energetically more favored than C20 and other nano-structures as reported in previous studies. It is expected that significant changes in the electronic properties caused by Rg may be used for designing new sensors for detection of rare gases.